(untitled) (Research, Society and Development, 2022)
Introduction: The abusive use of alcohol has harmful effects at different stages of life, generating mental and behavioral disorders of paramount importance. In addition, there is an exorbitant number of individuals who drink alcohol frequently and that may or may not result in abuse. Therefore, current data demonstrate the high mortality associated with the harmful use of alcohol, which raised many questions about the profile of this population. Objective: Identify the aspects involved in the epidemiology of the harmful use of alcohol in the city of Patos de Minas. Methodology: The present work consists of a descriptive, retrospective epidemiological study with a quantitative approach. A data research was carried out in the Informatics Department of the Unified Health System (DATASUS), analyzing all cases of hospitalizations for mental and behavioral disorders due to alcohol use in the city of Patos de Minas (MG), between 2010 and 2020. Discussion: The most expressive portion of the population were working age men. This fact highlights the most prevalent epidemiological profile, even with relative underreporting. Final considerations: In view of the more expressive epidemiological profile, health educational measures that aim to modify this epidemiological panel and mitigate the increase in cases and possible risks are necessary.